Kemampuan Berpikir Kritis Siswa Melalui Penerapan Pendekatan Realistic Mathematics Education Berbantuan Media Manipulatif Origami - Nur Fitri Amalia; Subanji Subanji; Sri Untari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This classroom action research aims to describe the success of the RME approach assisted by origami manipulative media to improve the critical thinking skills of VA class students at SDN 1 Patrang Jember. The study was conducted in two cycles. The research subjects were VA class students. Based on research in the first cycle showed that: (1) learning by teachers reached 89.7% and by students reached 88.5% (2) students' critical thinking skills reached 76.8%. The data in the first cycle have not yet reached the criteria for success of the action, so that improvements are made to the second cycle. In the second cycle showed that (1) teacher learning reached 95.9% and by students reached 93.2%, (2) students' critical thinking skills reached 88.9%. So it can be concluded that the RME approach assisted by origami manipulative media can improve students' critical thinking skills.Abstrak: Penelitian tindakan kelas ini bertujuan untuk mendeskripsikan keberhasilan pendekatan RME berbantuan media manipulatif origami meningkatkan kemampuan berpikir kritis siswa kelas VA SDN 1 Patrang Jember. Penelitian dilaksanakan dua siklus. Subjek penelitian yaitu siswa kelas VA. Berdasarkan penelitian siklus I menunjukkan bahwa (1) pembelajaran oleh guru mencapai 89,7% dan oleh siswa mencapai 88,5% (2) kemampuan berpikir kritis siswa mencapai 76,8%. Data siklus I tidak mencapai kriteria tindakan yang berhasil, sehingga dilaksanakan perbaikan dalam siklus II. Data siklus II menunjukkan (1) pembelajaran guru mencapai 95,9% dan oleh siswa mencapai 93,2%, (2) kemampuan. berpikir kritis siswa mencapai 88,9%. Dapat disimpulkan bahwa pendekatan RME berbantuan media manipulatif origami mampu meningkatkan kemampuan berpikir kritis siswa.